Characteristics of the vertical seismic waves associated with the 1995 Hyogo-ken Nanbu (Kobe), Japan earthquake estimated from the failure of the Daikai Underground Station. - Uenishi, Koji
The dynamic behaviour of underground structures built by cut and cover methods is discussed. A simple model analysis shows that a column supporting the overburden at midspan (central column) can resonate upon incidence of an elastic wave of a specific frequency. The analytical results indicate that not only the size and material properties of the column, but also the static load acting on the column (overburden) is a decisive factor that influences the resonant frequency. Based on the results obtained by the analysis, the mechanism of the failure at the Daikai Underground Station in Kobe caused by the 1995 Hyogo-ken Nanbu, Japan, earthquake is investigated. It is shown that the wave induced damage to underground structures can concentrate on the sections with specific overburden, and from the induced damage, it is possible to estimate the frequency characteristics of the associated seismic waves.
Keywords: Dynamic failure; Central column; Resonance of structures; Hyogo-ken Nambu earthquake; Daikai Station; Characteristics of seismic waves